Coordinated multi-sectoral efforts needed to address the COVID-19 pandemic: lessons from China and the United States - Zhuo Chen; Cong Cao; Gonghuan Yang (BMC, 2020)
Abstract The COVID-19 pandemic has caused staggering human and economic costs. We outline four key lessons learned from efforts to address the pandemic in China and the US. First, effective surveillance, reporting, and contact tracing are needed to contain an epidemic at its emergence and to mitigate its impact at a later stage. Second, multi-sectoral efforts to offer incentives for those with no or minor symptoms to seek care and to quarantine themselves are critical, which would need concerted efforts from payers, providers, and public health. Third, sustained and routine prevention efforts involving both the public and the health systems will prove to be useful in times of a pandemic. Fourth, a strong public health system is essential and will be appreciated at times of urgency. Concerted multi-sectoral efforts are required to address COVID-19 pandemic with strong leadership from the public health sector.